GLARE laminate structure residual fatigue life prediction method based on micro-nano sensor

By laying MXene/CNT micro-nano sensors at the interface between the metal layer and the fiber resin layer of the GLARE laminate, the structural strain state is monitored in real time and the damage stage is analyzed, the problem of difficult to predict the remaining fatigue life of the GLARE laminate in the prior art is solved, and high-precision structural health monitoring and residual life prediction are achieved.

CN119666346APending Publication Date: 2025-03-21SHENYANG AEROSPACE UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411849896.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively predict the remaining fatigue life of GLARE laminates, and the existing structural health monitoring technology has shortcomings in accuracy and real-time performance.

Method used

Using the method based on MXene/CNT micro-nano sensor, sensors are arranged at the interface between the metal layer and the fiber resin layer of the GLARE layer, the strain state of the structure is monitored in real time, and the damage stage is judged and the remaining fatigue life is predicted by analyzing the sensor data.

Benefits of technology

High-precision real-time monitoring of the GLARE laminate structure is realized, which can accurately judge the damage stage and predict the remaining fatigue life, avoid signal delays and errors in traditional methods, and improve the safety and reliability of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119666346A_ABST
    Figure CN119666346A_ABST
Patent Text Reader

Abstract

The invention provides a GLARE laminate structure residual fatigue life prediction method based on a micro-nano sensor, and relates to the technical field of structure health monitoring. MXene / CNT sensors are arranged on the outer surface of a metal layer of a GLARE laminate, the interface of the metal layer and a fiber resin layer or the position between fiber layers; the resin in the composite prepreg permeates into the middle of the MXene sheet layer and pores of the CNT, so that the sensor and the tested laminated plate test piece are integrally cured and molded; therefore, the sensor can perform high-sensitivity and high-precision real-time monitoring on the strain and damage conditions of the whole structure, the metal-fiber resin layer interface and the fiber layers in the service process of the GLARE laminate structure. And predicting the residual fatigue life of the GLARE laminate by statistically analyzing the sensor resistance change rate of the GLARE laminate in the early stage of damage initiation, the stable expansion period of the crack and the unstable expansion period of the crack.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of structural health monitoring, and in particular to a method for predicting the residual fatigue life of a GLARE laminate structure based on a micro-nano sensor. Background Art

[0002] Glass Reinforced Aluminum Laminates (GLARE Laminates) are widely used in aviation, aerospace, shipbuilding, railways and other fields due to their low density, high strength, excellent fatigue resistance, impact resistance and high damage tolerance. In the current era of pursuing lightweight design and damage tolerance of aircraft, GLARE laminates are particularly widely used in the aerospace field. In view of the bridging effect between fiber-reinforced composite materials and metals, the crack growth rate of GLARE laminates is much lower than that of aluminum alloy plates, making them have a very high damage tolerance. However, GLARE laminates are different from traditional metal plates or fiber-reinforced composite laminates. They are sandwich structures formed by alternating metal and composite materials. Due to the anisotropic characteristics of fiber-reinforced composite materials themselves and the interaction of crack evolution, layered growth and bridging stress when damage occurs at the metal-composite interface, GLARE laminates have multiple damage modes, the interlayer stress state is also very complex, and structural damage is difficult to be discovered in time. In actual engineering applications, issues such as cost must be taken into consideration, which requires evaluating whether the component needs to be replaced based on the remaining life of the structural component. Therefore, it is very necessary to design a method that can effectively predict the remaining fatigue life of the GLARE laminate.

[0003] In order to determine the structural integrity and residual fatigue life of GLARE laminates, non-destructive testing technology and structural health monitoring technology are currently mainly used in engineering. Although non-destructive testing technology can effectively detect the damage morphology of the structure, it is not real-time and needs to be tested when the equipment is shut down, which affects the normal service of the structural parts. For structural health monitoring technology, the fiber optic detection method and strain gauge detection method are widely used in engineering. Although the fiber optic detection method can effectively monitor the damage of GLARE laminates in real time, the fiber size is nearly two orders of magnitude larger than the fiber diameter, and the bonding degree with the resin is low. It can only be arranged on the surface of the composite material structure. If it is embedded inside, it is equivalent to introducing new defects in the structure, which will lead to a decrease in the overall mechanical properties of the structure. In the strain gauge detection method, since the strain gauge needs to be attached to the GLARE laminate through an adhesive, an intermediate interface will be generated between the sensing element and the tested piece, resulting in delays and errors in the detection signal. In addition, the strain gauge is not compatible with the integrated composite structure and can only be arranged on the surface of the structure. The detection accuracy of internal damage is poor or cannot be detected. Moreover, most current detection methods can only determine the current damage state of the structure, but cannot give early warning of impending dangerous damage, nor can they predict the remaining fatigue life of structural parts. Therefore, in order to ensure the normal operation of GLARE laminate structural parts in the project, an effective method for predicting the remaining fatigue life of GLARE laminate is urgently needed.

[0004] Carbon nanotubes (CNTs) are one-dimensional quantum materials with a special structure. Their radial dimensions are in the nanometer range and their axial dimensions are in the micrometer range. They are mainly composed of several to dozens of layers of coaxial circular tubes of carbon atoms arranged in a hexagonal pattern. The resin in the GLARE laminate can effectively infiltrate the carbon nanotubes, thereby achieving an integrated molding effect, and will not affect the mechanical properties of the GLARE laminate structure. The sensor made by CNT self-assembly has high sensitivity and recoverability, and can effectively monitor the tiny strains of the structure. Based on the one-dimensional CNT structure sensor, patent CN 201911336931.8 "A sensor and preparation method for monitoring the liquid molding process of composite materials" introduces carbon / nitride two-dimensional nanolayered materials (MXene) to form a highly sensitive and high-precision three-dimensional conductive network MXene / CNT sensor, which can be deployed at different positions on the surface or inside of any shape of composite material / metal structure. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a method for predicting the residual fatigue life of a GLARE laminate structure based on micro-nano sensors. The strain state of the GLARE laminate can be monitored online in real time through the sensor, and the damage stage of the structure can be effectively analyzed according to the sensor data response to predict the residual fatigue life.

[0006] A method for predicting the residual fatigue life of a GLARE laminate structure based on micro-nano sensors comprises the following steps:

[0007] Step 1: Grind the surface of the metal plate with sandpaper, clean the surface of the metal plate with ethanol, hydrochloric acid solution and sodium hydroxide solution, and perform surface treatment;

[0008] The metal plate is made of 2 series or 7 series aluminum alloy plate;

[0009] The grinding is carried out using 100-grit sandpaper;

[0010] The surface treatment is surface anodizing or surface acid treatment.

[0011] Step 2: Prepare MXene / CNT micro-nano sensor, connect the micro-nano sensor with a flexible printed circuit through a conductive silver paste to obtain a micro-nano sensor unit;

[0012] In the step 2, after the micro-nano sensor is connected to the flexible printed circuit, it is dried in an oven at 110° C. for 1 to 2 hours;

[0013] Step 3: alternately ply the metal plate and the glass fiber prepreg to obtain a GLARE laminate structure, and arrange the micro-nano sensor unit inside the GLARE laminate, solidify the micro-nano sensor and the GLARE laminate as one, and then paste the micro-nano sensor unit on the metal layer on the outer surface of the GLARE laminate;

[0014] Step 3.1: alternately ply the treated metal plate and the glass fiber prepreg to obtain a GLARE laminate structure, and during the plying process, arrange the micro-nano sensor unit at the interface between the metal layer and the fiber resin layer or between the fiber resin layers;

[0015] Step 3.2: Place the GLARE laminate with the embedded micro-nano sensor unit in a hot press for heating and pressurizing to cure. After curing, naturally cool to room temperature for demoulding. Then, paste the micro-nano sensor unit on the metal layer on the outer surface of the GLARE laminate.

[0016] The MXene-CNT-MXene sandwich structure film in the MXene / CNT micro-nano sensor is cut into a circular shape with a diameter of 2 to 10 mm and a thickness of 15 to 30 μm according to actual needs. The micro-nano sensor unit is arranged at the interface between the metal layer and the fiber resin layer of the GLARE laminate, and the micro-nano sensor units at other positions are arranged on the outer surface of the laminate or between the fiber layers according to actual needs. The micro-nano sensor unit arranged inside the GLARE laminate is melted and then solidified by the resin in the glass fiber prepreg during the hot pressing process; the micro-nano sensor unit arranged on the outer surface of the GLARE laminate needs to be fixed to the metal surface with an epoxy resin adhesive, and the coating thickness of the adhesive is between 0.05 and 0.15 mm;

[0017] During the curing process, the curing pressure, temperature and curing time are selected according to the curing parameters of the selected glass fiber prepreg.

[0018] Step 4: Perform fatigue test on the GLARE laminate, determine the damage stage of the GLARE laminate according to the response of the sensor, and obtain the remaining fatigue life of the GLARE laminate when it is in the stable crack extension stage and the unstable crack extension stage by linear fitting.

[0019] Step 4.1: Perform fatigue test on the cured GLARE laminate. When the sensor resistance change rate-cycle number curve shows an upward trend with a constant slope, it indicates that the laminate has entered the stable crack extension stage. When the slope of its resistance change rate-cycle number curve begins to increase, it indicates that the laminate has entered the unstable crack extension stage. When the resistance change rate-cycle number curve suddenly increases, it indicates that the laminate has suffered overall fracture failure.

[0020] Step 4.2: The initial resistance value of the sensor unit arranged on the GLARE layer is recorded as R0; the real-time resistance change of the sensor unit is recorded as ΔR, that is, the real-time resistance value R minus the initial resistance value R0; the real-time resistance change rate of the sensor unit is recorded as ΔR / R0; the resistance change rate when the layer enters the stable crack expansion stage is recorded as ΔR / R 0(S) The resistance change rate of the laminate at the critical point between stable and unstable crack extension is recorded as ΔR / R 0(M) The resistance change rate before the fatigue fracture of the laminate is recorded as ΔR / R 0(U) When the laminate is in the stable crack extension stage, the residual fatigue life of the laminate is predicted according to formula (1); when the laminate is in the unstable crack extension stage, the residual fatigue life of the laminate is predicted according to formula (2).

[0021]

[0022] Where F ris the remaining fatigue times of GLARE laminate, F S F is the total number of fatigue cycles that the crack can withstand during the stable expansion stage. U It is the total number of fatigue cycles that the crack can withstand during the unstable expansion stage.

[0023] In step 4, when performing fatigue testing, a resistance measuring instrument is connected to the flexible printed circuit of the sensor, and the acquisition frequency of the resistance measuring instrument needs to be greater than the fatigue load frequency;

[0024] The beneficial effects of adopting the above technical solution are:

[0025] The present invention provides a method for predicting the residual fatigue life of a GLARE laminate structure based on a micro-nano sensor, and the specific beneficial effects are as follows:

[0026] (1) The advantage of this monitoring method is that the MXene / CNT sensor is a sheet-tube cross-linked porous structure, and the resin of the prepreg in the GLARE layer can penetrate into the sensor for integrated molding, thereby providing real-time feedback on the mechanical behavior and damage state of the structure. Compared with traditional strain gauges and other monitoring methods, the integrated sensor is arranged inside the component without causing its organizational changes and structural defects. In addition, there is no stress transfer interface such as an adhesive layer between the sensor arranged inside the structure and the test piece, thus achieving high-precision real-time monitoring without response signal delay.

[0027] (2) The present invention uses MXene / CNT sensors to monitor the mechanical behavior of the GLARE laminate structure and predict the remaining fatigue life. The sensors are inexpensive, the monitoring system is easy to build and operate, and the response signal processing method is simple. By recording the current resistance change rate and substituting it into formulas (1) and (2), the remaining fatigue life of the component can be calculated, thereby evaluating the safety and reliability of the structure's continued service. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the arrangement of the GLARE layer sensor of the present invention;

[0029] Wherein: 1-metal plate, 2-glass fiber prepreg, 3-micro-nano sensor unit 3;

[0030] Figure 2 This is a graph showing fatigue damage response of a GLARE laminate monitored by a sensor in an embodiment of the present invention;

[0031] Figure 3 It is a partial enlarged view of the fatigue damage response curve of the GLARE laminate monitored by the sensor in the embodiment of the present invention. DETAILED DESCRIPTION

[0032] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.

[0033] A method for predicting the remaining fatigue life of a GLARE laminate structure based on micro-nano sensors. The schematic diagram of the arrangement of the GLARE laminate sensors in the embodiment is shown in FIG. Figure 1 As shown, the following steps are included:

[0034] Embodiment 1:

[0035] Step 1: Use 100-grit sandpaper to polish the surface of 2024-T3 aluminum alloy to remove the surface oxide layer, use ethanol, hydrochloric acid solution and sodium hydroxide solution to clean the surface of the aluminum plate to remove surface impurities, and perform phosphoric acid anodizing treatment at a voltage of 10V with a phosphoric acid concentration of 0.4wt% to make the metal layer and the fiber resin layer have a higher degree of bonding.

[0036] Step 2: Use patent CN 201911336931.8 "A sensor and preparation method for monitoring the liquid forming process of composite materials" to prepare a MXene / CNT sensor. The MXene-CNT-MXene sandwich structure film in the MXene / CNT sensor is a circular shape with a diameter of 5 mm and a thickness of 20 μm.

[0037] Step 3: alternately ply the metal plate 1 and the glass fiber prepreg 2 to obtain a GLARE laminate structure, and arrange the micro-nano sensor unit 3 inside the GLARE laminate, solidify the micro-nano sensor and the GLARE laminate as one, and then paste the micro-nano sensor unit on the metal layer on the outer surface of the GLARE laminate;

[0038] In this embodiment, the glass fiber epoxy prepreg is cut to the same size as the aluminum plate layer, and is alternately layered with the aluminum plate. The sensor is arranged at the interface between the metal layer and the fiber resin layer. A hot press is used to cure for 2 hours at 120°C and 2MPa pressure. The sensor is fixed in position by melting and then curing the epoxy resin in the glass fiber prepreg. After the GLARE layer is cured, stop heating and let it cool naturally to room temperature for demoulding.

[0039] Step 3.1: alternately ply the treated metal plate and the glass fiber prepreg to obtain a GLARE laminate structure, and during the plying process, arrange the micro-nano sensor unit at the interface between the metal layer and the fiber resin layer or between the fiber resin layers;

[0040] Step 3.2: Place the GLARE laminate with the embedded micro-nano sensor unit in a hot press for heating and pressurizing to cure. After curing, naturally cool to room temperature for demoulding. Then, paste the micro-nano sensor unit on the metal layer on the outer surface of the GLARE laminate.

[0041] The MXene-CNT-MXene sandwich structure film in the MXene / CNT micro-nano sensor is cut into a circular shape with a diameter of 2 to 10 mm and a thickness of 15 to 30 μm according to actual needs. The micro-nano sensor unit is arranged at the interface between the metal layer and the fiber resin layer of the GLARE laminate, and the micro-nano sensor units at other positions are arranged on the outer surface of the laminate or between the fiber layers according to actual needs to monitor their strain state. The micro-nano sensor unit arranged inside the GLARE laminate can be fixed in position during the hot pressing process by melting and solidifying the resin in the glass fiber prepreg; the micro-nano sensor unit arranged on the outer surface of the GLARE laminate needs to be fixed to the metal surface with epoxy resin adhesive to prevent the sensor from falling off. The thickness of the adhesive is between 0.05-0.15 mm to prevent the adhesive layer from being too thick to cause stress concentration and cause monitoring errors.

[0042] During the curing process, the curing pressure, temperature and curing time are selected according to the curing parameters of the selected glass fiber prepreg.

[0043] Step 4: Perform fatigue test on the GLARE laminate, determine the damage stage of the GLARE laminate according to the response of the sensor, and obtain the remaining fatigue life of the GLARE laminate when it is in the stable crack extension stage and the unstable crack extension stage by linear fitting. Figure 2 Sensor monitoring data for the entire process, Figure 3 for Figure 2 A partial enlarged view of the structure at the crack-free stage, crack initiation, stable crack extension stage, and unstable crack extension stage. Figure 3 It can be seen that when no crack occurs in the GLARE laminate, the sensor resistance change rate fluctuates very little and is close to zero. When the crack initiates, the sensor resistance change rate fluctuates slightly in the range close to zero. In the stable crack expansion stage, the sensor resistance change rate increases slowly, and in the unstable crack expansion stage, the sensor resistance change rate increases rapidly.

[0044] Step 4.1: Fatigue test is performed on the cured GLARE laminate. The sensor resistance will fluctuate stably within a certain range close to zero in the undamaged stage and the early stage of damage of the test piece. When the sensor resistance change rate-cycle number curve shows an upward trend with a constant slope, it indicates that the laminate has entered the stable crack extension stage. When the slope of its resistance change rate-cycle number curve begins to increase, it indicates that the laminate has entered the unstable crack extension stage. When the resistance change rate-cycle number curve suddenly increases, it indicates that the laminate has suffered overall fracture failure.

[0045] Step 4.2: The initial resistance value of the sensor unit arranged on the GLARE layer is recorded as R0; the real-time resistance change of the sensor unit is recorded as ΔR, that is, the real-time resistance value R minus the initial resistance value R0; the real-time resistance change rate of the sensor unit is recorded as ΔR / R0; the resistance change rate when the layer enters the stable crack expansion stage is recorded as ΔR / R 0(S) The resistance change rate of the laminate at the critical point between stable and unstable crack extension is recorded as ΔR / R 0(M) The resistance change rate before the fatigue fracture of the laminate is recorded as ΔR / R 0(U) When the laminate is in the stable crack extension stage, the remaining fatigue life of the laminate is predicted according to formula (1); when the laminate is in the unstable crack extension stage, the remaining fatigue life of the laminate is predicted according to formula (2).

[0046]

[0047] Where F r is the remaining fatigue times of GLARE laminate, F S F is the total number of fatigue cycles that the crack can withstand during the stable expansion stage. U It is the total number of fatigue cycles that the crack can withstand during the unstable expansion stage.

[0048] In step 4, when the GLARE laminate is subjected to a tensile load in a fatigue test, the contact area between the mutually contacting MXene sheets and CNTs inside the arranged sensor element decreases, causing the contact resistance to increase; the distance between the non-contacting MXene sheets and CNTs increases, causing the potential barrier between them to become larger, the tunneling current to decrease, and the tunneling resistance to increase. During the unloading process of the fatigue test, the MXene sheets and CNTs inside the sensor element arranged by the GLARE laminate gradually return to their initial positions, so that the sensor resistance rebounds to the initial value. Therefore, by monitoring the sensor resistance and its rate of change, the load state of the GLARE laminate structure can be fed back in real time.

[0049] In the step 4, when performing fatigue test, a resistance measuring instrument is connected to the flexible printed circuit of the sensor, and the acquisition frequency of the resistance measuring instrument needs to be greater than the fatigue load frequency;

[0050] In the step 4, the progressive damage evolution of the GLARE laminate under the action of fatigue load will go through five stages: no damage stage - crack initiation - stable crack extension - unstable crack extension - overall structural fracture failure. In the no crack damage stage, the resistance change rate of the sensor fluctuates very little and is close to zero; when the crack initiates, due to the existence of the bridging effect between the metal layer and the fiber resin layer, the structure will not produce obvious local strain near the crack, and the resistance change rate of the sensor fluctuates slightly in the vicinity of zero; when the structure is in the stable crack extension stage, the local strain of the structure increases, which leads to an upward trend in the resistance change rate, but due to the slow crack extension rate, the rising speed of the sensor resistance change rate is also relatively slow at this time; when the structure enters the unstable crack extension stage, a gradually increasing local displacement will occur near the crack, resulting in a rapid upward trend in the sensor resistance change rate; when the structure fails to fracture as a whole, the sensor resistance change rate increases suddenly.

[0051] Embodiment 2:

[0052] Step 1: Use 100-grit sandpaper to polish the surface of 7075-T6 aluminum alloy to remove the surface oxide layer, use ethanol, hydrochloric acid solution and sodium hydroxide solution to clean the surface of the aluminum plate to remove surface impurities, and perform phosphoric acid anodizing treatment at a voltage of 10V with a phosphoric acid concentration of 0.4wt%, so that the metal and the fiber layer have a higher degree of bonding.

[0053] Step 2: Use patent CN 201911336931.8 "A sensor and preparation method for monitoring the liquid forming process of composite materials" to prepare a MXene / CNT sensor. The MXene-CNT-MXene sandwich structure film in the MXene / CNT sensor is a circular shape with a diameter of 10 mm and a thickness of 30 μm.

[0054] Step 3: alternately ply the metal plate 1 and the glass fiber prepreg 2 to obtain a GLARE laminate structure, and arrange the micro-nano sensor unit 3 inside the GLARE laminate, solidify the micro-nano sensor and the GLARE laminate as one, and then paste the micro-nano sensor unit on the metal layer on the outer surface of the GLARE laminate;

[0055] In this embodiment, the glass fiber epoxy prepreg is cut to the same size as the aluminum plate layer, and alternately layered with the aluminum plate. The sensors are arranged at the interface between the aluminum plate and the glass fiber resin layer and the outer surface of the GLARE layer. A hot press is used to cure for 1 hour at 140°C and 1.5MPa pressure. The sensor at the interface of the aluminum plate and the glass fiber resin layer can be fixed in position by melting and then solidifying the epoxy resin in the glass fiber prepreg. After the GLARE layer is cured, stop heating and let it cool naturally to room temperature for demoulding. Then apply 0.1mm thick epoxy resin adhesive on the outer surface of the aluminum plate of the GLARE layer, stick the sensor on the outer surface of the aluminum plate, and remove the excess adhesive.

[0056] Step 3.1: alternately ply the treated metal plate and the glass fiber prepreg to obtain a GLARE laminate structure, and during the plying process, arrange the micro-nano sensor unit at the interface between the metal layer and the fiber resin layer or between the fiber resin layers;

[0057] Step 3.2: Place the GLARE laminate with the embedded micro-nano sensor unit in a hot press for heating and pressurizing to cure. After curing, naturally cool to room temperature for demoulding. Then, paste the micro-nano sensor unit on the metal layer on the outer surface of the GLARE laminate.

[0058] The MXene-CNT-MXene sandwich structure film in the MXene / CNT micro-nano sensor is cut into a circular shape with a diameter of 2 to 10 mm and a thickness of 15 to 30 μm according to actual needs. The micro-nano sensor unit is arranged at the interface between the metal layer and the fiber resin layer of the GLARE laminate, and the micro-nano sensor units at other positions are arranged on the outer surface of the laminate or between the fiber layers according to actual needs to monitor their strain state. The micro-nano sensor unit arranged inside the GLARE laminate can be fixed in position during the hot pressing process by melting and solidifying the resin in the glass fiber prepreg; the micro-nano sensor unit arranged on the outer surface of the GLARE laminate needs to be fixed to the metal surface with epoxy resin adhesive to prevent the sensor from falling off. The thickness of the adhesive is between 0.05-0.15 mm to prevent the adhesive layer from being too thick to cause stress concentration and cause monitoring errors.

[0059] During the curing process, the curing pressure, temperature and curing time are selected according to the curing parameters of the selected glass fiber prepreg.

[0060] Step 4: Perform fatigue test on the GLARE laminate, determine the damage stage of the GLARE laminate according to the response of the sensor, and obtain the calculation method of the remaining fatigue life of the GLARE laminate when it is in the stable crack extension stage and the unstable crack extension stage by linear fitting. Figure 2 Sensor monitoring data for the entire process, Figure 3 for Figure 2 A partial enlarged view of the structure at the crack-free stage, crack initiation, stable crack extension stage, and unstable crack extension stage. Figure 3 It can be seen that when no crack occurs in the GLARE laminate, the sensor resistance change rate fluctuates very little and is close to zero. When the crack initiates, the sensor resistance change rate fluctuates slightly in the range close to zero. In the stable crack expansion stage, the sensor resistance change rate increases slowly, and in the unstable crack expansion stage, the sensor resistance change rate increases rapidly.

[0061] Step 4.1: Fatigue test is performed on the cured GLARE laminate. The sensor resistance will fluctuate stably within a certain range close to zero in the undamaged stage and the early stage of damage of the test piece. When the sensor resistance change rate-cycle number curve shows an upward trend with a constant slope, it indicates that the laminate has entered the stable crack extension stage. When the slope of its resistance change rate-cycle number curve begins to increase, it indicates that the laminate has entered the unstable crack extension stage. When the resistance change rate-cycle number curve suddenly increases, it indicates that the laminate has suffered overall fracture failure.

[0062] Step 4.2: The initial resistance value of the sensor unit arranged on the GLARE layer is recorded as R0; the real-time resistance change of the sensor unit is recorded as ΔR, that is, the real-time resistance value R minus the initial resistance value R0; the real-time resistance change rate of the sensor unit is recorded as ΔR / R0; the resistance change rate when the layer enters the stable crack expansion stage is recorded as ΔR / R 0(S) The resistance change rate of the laminate at the critical point between stable and unstable crack extension is recorded as ΔR / R 0(M) The resistance change rate before the fatigue fracture of the laminate is recorded as ΔR / R 0(U) When the laminate is in the stable crack extension stage, the remaining fatigue life of the laminate is predicted according to formula (1); when the laminate is in the unstable crack extension stage, the remaining fatigue life of the laminate is predicted according to formula (2).

[0063]

[0064] Where F r is the remaining fatigue times of GLARE laminate, F S F is the total number of fatigue cycles that the crack can withstand during the stable expansion stage. U It is the total number of fatigue cycles that the crack can withstand during the unstable expansion stage.

[0065] In step 4, when the GLARE laminate is subjected to a tensile load in a fatigue test, the contact area between the mutually contacting MXene sheets and CNTs inside the arranged sensor element decreases, causing the contact resistance to increase; the distance between the non-contacting MXene sheets and CNTs increases, causing the potential barrier between them to become larger, the tunneling current to decrease, and the tunneling resistance to increase. During the unloading process of the fatigue test, the MXene sheets and CNTs inside the sensor element arranged by the GLARE laminate gradually return to their initial positions, so that the sensor resistance rebounds to the initial value. Therefore, by monitoring the sensor resistance and its rate of change, the load state of the GLARE laminate structure can be fed back in real time.

[0066] In the step 4, when performing fatigue test, a resistance measuring instrument is connected to the flexible printed circuit of the sensor, and the acquisition frequency of the resistance measuring instrument needs to be greater than the fatigue load frequency;

[0067] In the step 4, the progressive damage evolution of the GLARE laminate under the action of fatigue load will go through five stages: no damage stage - crack initiation - stable crack extension - unstable crack extension - overall structural fracture failure. In the no crack damage stage, the resistance change rate of the sensor fluctuates very little and is close to zero; when the crack initiates, due to the existence of the bridging effect between the metal layer and the fiber resin layer, the structure will not produce obvious local strain near the crack, and the resistance change rate of the sensor fluctuates slightly in the vicinity of zero; when the structure is in the stable crack extension stage, the local strain of the structure increases, which leads to an upward trend in the resistance change rate, but due to the slow crack extension rate, the rising speed of the sensor resistance change rate is also relatively slow at this time; when the structure enters the unstable crack extension stage, a gradually increasing local displacement will occur near the crack, resulting in a rapid upward trend in the sensor resistance change rate; when the structure fails to fracture as a whole, the sensor resistance change rate increases suddenly.

[0068] Embodiment 3:

[0069] Step 1: Use 100-grit sandpaper to polish the surface of 2024-T3 aluminum alloy to remove the surface oxide layer, use ethanol, hydrochloric acid solution and sodium hydroxide solution to clean the surface of the aluminum plate to remove surface impurities, and perform phosphoric acid anodizing treatment at a voltage of 10V with a phosphoric acid concentration of 0.4wt%, so that the metal and the fiber layer have a higher degree of bonding.

[0070] Step 2: Use patent CN 201911336931.8 "A sensor and preparation method for monitoring the liquid forming process of composite materials" to prepare a MXene / CNT sensor. The MXene-CNT-MXene sandwich structure film in the MXene / CNT sensor is a circular shape with a diameter of 2 mm and a thickness of 15 μm.

[0071] Step 3: alternately ply the metal plate 1 and the glass fiber prepreg 2 to obtain a GLARE laminate structure, and arrange the micro-nano sensor unit 3 inside the GLARE laminate, solidify the micro-nano sensor and the GLARE laminate as one, and then paste the micro-nano sensor unit on the metal layer on the outer surface of the GLARE laminate;

[0072] In this embodiment, the glass fiber epoxy prepreg is cut to the same size as the aluminum plate layer and alternately layered with the aluminum plate. The sensor is arranged at the interface between the aluminum plate and the glass fiber resin layer and between two adjacent layers of glass fiber prepreg. A hot press is used to cure for 1.5 hours at 130°C and 2MPa pressure. The sensor is fixed in position by melting and then curing the epoxy resin in the glass fiber prepreg. After the GLARE layer is cured, stop heating and let it cool naturally to room temperature for demoulding.

[0073] Step 3.1: alternately ply the treated metal plate and the glass fiber prepreg to obtain a GLARE laminate structure, and during the plying process, arrange the micro-nano sensor unit at the interface between the metal layer and the fiber resin layer or between the fiber resin layers;

[0074] Step 3.2: Place the GLARE laminate with the embedded micro-nano sensor unit in a hot press for heating and pressurizing to cure. After curing, naturally cool to room temperature for demoulding. Then, paste the micro-nano sensor unit on the metal layer on the outer surface of the GLARE laminate.

[0075] The MXene-CNT-MXene sandwich structure film in the MXene / CNT micro-nano sensor is cut into a circular shape with a diameter of 2 to 10 mm and a thickness of 15 to 30 μm according to actual needs. The micro-nano sensor unit is arranged at the interface between the metal layer and the fiber resin layer of the GLARE laminate, and the micro-nano sensor units at other positions are arranged on the outer surface of the laminate or between the fiber layers according to actual needs to monitor their strain state. The micro-nano sensor unit arranged inside the GLARE laminate can be fixed in position during the hot pressing process by melting and solidifying the resin in the glass fiber prepreg; the micro-nano sensor unit arranged on the outer surface of the GLARE laminate needs to be fixed to the metal surface with epoxy resin adhesive to prevent the sensor from falling off. The thickness of the adhesive is between 0.05-0.15 mm to prevent the adhesive layer from being too thick to cause stress concentration and cause monitoring errors.

[0076] During the curing process, the curing pressure, temperature and curing time are selected according to the curing parameters of the selected glass fiber prepreg.

[0077] Step 4: Perform fatigue test on the GLARE laminate, determine the damage stage of the GLARE laminate according to the response of the sensor, and obtain the calculation method of the remaining fatigue life of the GLARE laminate when it is in the stable crack extension stage and the unstable crack extension stage by linear fitting. Figure 2 Sensor monitoring data for the entire process, Figure 3 for Figure 2 A partial enlarged view of the structure at the crack-free stage, crack initiation, stable crack extension stage, and unstable crack extension stage. Figure 3 It can be seen that when no crack occurs in the GLARE laminate, the sensor resistance change rate fluctuates very little and is close to zero. When the crack initiates, the sensor resistance change rate fluctuates slightly in the range close to zero. In the stable crack expansion stage, the sensor resistance change rate increases slowly, and in the unstable crack expansion stage, the sensor resistance change rate increases rapidly.

[0078] Step 4.1: Fatigue test is performed on the cured GLARE laminate. The sensor resistance will fluctuate stably within a certain range close to zero in the undamaged stage and the early stage of damage of the test piece. When the sensor resistance change rate-cycle number curve shows an upward trend with a constant slope, it indicates that the laminate has entered the stable crack extension stage. When the slope of its resistance change rate-cycle number curve begins to increase, it indicates that the laminate has entered the unstable crack extension stage. When the resistance change rate-cycle number curve suddenly increases, it indicates that the laminate has suffered overall fracture failure.

[0079] Step 4.2: The initial resistance value of the sensor unit arranged on the GLARE layer is recorded as R0; the real-time resistance change of the sensor unit is recorded as ΔR, that is, the real-time resistance value R minus the initial resistance value R0; the real-time resistance change rate of the sensor unit is recorded as ΔR / R0; the resistance change rate when the layer enters the stable crack expansion stage is recorded as ΔR / R 0(S) The resistance change rate of the laminate at the critical point between stable and unstable crack extension is recorded as ΔR / R 0(M) The resistance change rate before the fatigue fracture of the laminate is recorded as ΔR / R 0(U) When the laminate is in the stable crack extension stage, the remaining fatigue life of the laminate is predicted according to formula (1); when the laminate is in the unstable crack extension stage, the remaining fatigue life of the laminate is predicted according to formula (2).

[0080]

[0081] Where F r is the remaining fatigue times of GLARE laminate, F S F is the total number of fatigue cycles that the crack can withstand during the stable expansion stage. U It is the total number of fatigue cycles that the crack can withstand during the unstable expansion stage.

[0082] In step 4, when the GLARE laminate is subjected to a tensile load in a fatigue test, the contact area between the mutually contacting MXene sheets and CNTs inside the arranged sensor element decreases, causing the contact resistance to increase; the distance between the non-contacting MXene sheets and CNTs increases, causing the potential barrier between them to become larger, the tunneling current to decrease, and the tunneling resistance to increase. During the unloading process of the fatigue test, the MXene sheets and CNTs inside the sensor element arranged by the GLARE laminate gradually return to their initial positions, so that the sensor resistance rebounds to the initial value. Therefore, by monitoring the sensor resistance and its rate of change, the load state of the GLARE laminate structure can be fed back in real time.

[0083] In the step 4, when performing fatigue test, a resistance measuring instrument is connected to the flexible printed circuit of the sensor, and the acquisition frequency of the resistance measuring instrument needs to be greater than the fatigue load frequency;

[0084] In the step 4, the progressive damage evolution of the GLARE laminate under the action of fatigue load will go through five stages: no damage stage - crack initiation - stable crack extension - unstable crack extension - overall structural fracture failure. In the no crack damage stage, the resistance change rate of the sensor fluctuates very little and is close to zero; when the crack initiates, due to the existence of the bridging effect between the metal layer and the fiber resin layer, the structure will not produce obvious local strain near the crack, and the resistance change rate of the sensor fluctuates slightly in the vicinity of zero; when the structure is in the stable crack extension stage, the local strain of the structure increases, which leads to an upward trend in the resistance change rate, but due to the slow crack extension rate, the rising speed of the sensor resistance change rate is also relatively slow at this time; when the structure enters the unstable crack extension stage, a gradually increasing local displacement will occur near the crack, resulting in a rapid upward trend in the sensor resistance change rate; when the structure fails to fracture as a whole, the sensor resistance change rate increases suddenly.

[0085] In summary, in the residual fatigue life prediction method of the GLARE laminate structure based on micro-nano sensors in this patent, the sensor can be arranged at the interface between the metal layer and the fiber resin layer. In addition, sensors can be appropriately arranged on the outer surface of the GLARE laminate or between the internal fiber layers as needed to perform real-time damage monitoring and residual fatigue life prediction of the GLARE laminate. This monitoring method is simple to operate, convenient and practical, low-cost, does not affect the original performance of the tested component, makes up for the shortcomings of non-destructive testing, and provides an effective method for real-time monitoring and residual fatigue life prediction of GLARE laminates.

[0086] The above description is only a preferred embodiment of the present disclosure and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the embodiments of the present disclosure is not limited to the technical solutions formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the above-mentioned inventive concept. For example, the above-mentioned features are replaced with the technical features with similar functions disclosed in the embodiments of the present disclosure (but not limited to) to form a technical solution.

Claims

1. A method for predicting the residual fatigue life of a GLARE laminate structure based on micro-nano sensors, characterized in that: The following steps are involved: Step 1: Grind the surface of the metal plate with sandpaper, clean the surface of the metal plate with ethanol, hydrochloric acid solution and sodium hydroxide solution, and perform surface treatment; Step 2: Prepare MXene / CNT micro-nano sensor, connect the micro-nano sensor with a flexible printed circuit through a conductive silver paste to obtain a micro-nano sensor unit; Step 3: alternately ply the metal plate and the glass fiber prepreg to obtain a GLARE laminate structure, and arrange the micro-nano sensor unit inside the GLARE laminate, solidify the micro-nano sensor and the GLARE laminate as one, and then paste the micro-nano sensor unit on the metal layer on the outer surface of the GLARE laminate; Step 4: Perform fatigue test on the GLARE laminate, determine the damage stage of the GLARE laminate according to the response of the sensor, and obtain the remaining fatigue life of the GLARE laminate when it is in the stable crack extension stage and the unstable crack extension stage by linear fitting.

2. The method for predicting the residual fatigue life of a GLARE laminate structure based on micro-nano sensors according to claim 1 is characterized in that: The metal plate in step 1 is a 2 series or 7 series aluminum alloy plate; The grinding is carried out using 100-grit sandpaper; The surface treatment is surface anodizing or surface acid treatment.

3. The method for predicting the residual fatigue life of a GLARE laminate structure based on micro-nano sensors according to claim 1 is characterized in that: In the step 2, after the micro-nano sensor is connected to the flexible printed circuit, it is dried in an oven at 110° C. for 1 to 2 hours.

4. The method for predicting the residual fatigue life of a GLARE laminate structure based on micro-nano sensors according to claim 1 is characterized in that: The step 3 specifically comprises the following steps: Step 3.1: alternately ply the treated metal plate and the glass fiber prepreg to obtain a GLARE laminate structure, and during the plying process, arrange the micro-nano sensor unit at the interface between the metal layer and the fiber resin layer or between the fiber resin layers; Step 3.2: Place the GLARE laminate with the embedded micro-nano sensor unit in a hot press for heating and pressurizing to cure. After curing, naturally cool to room temperature and demold. Then, paste the micro-nano sensor unit on the metal layer on the outer surface of the GLARE laminate.

5. The method for predicting the residual fatigue life of a GLARE laminate structure based on micro-nano sensors according to claim 4 is characterized in that: The MXene-CNT-MXene sandwich structure film in the MXene / CNT micro-nano sensor is cut into a circular shape with a diameter of 2 to 10 mm and a thickness of 15 to 30 μm according to actual needs. The micro-nano sensor unit is arranged at the interface between the metal layer and the fiber resin layer of the GLARE layer, and the micro-nano sensor units at other positions are arranged on the outer surface of the laminate or between the fiber layers according to actual needs. The micro-nano sensor units arranged inside the GLARE layer are melted and then solidified by the resin in the glass fiber prepreg during the hot pressing process; the micro-nano sensor units arranged on the outer surface of the GLARE layer need to be fixed to the metal surface with an epoxy resin adhesive, and the coating thickness of the adhesive is between 0.05 and 0.15 mm.

6. The method for predicting the residual fatigue life of a GLARE laminate structure based on micro-nano sensors according to claim 4, characterized in that: During the curing process, the curing pressure, temperature and curing time are selected according to the curing parameters of the selected glass fiber prepreg.

7. The method for predicting the residual fatigue life of a GLARE laminate structure based on micro-nano sensors according to claim 1, characterized in that: The step 4 specifically comprises the following steps: Step 4.1: Perform fatigue test on the cured GLARE laminate. When the sensor resistance change rate-cycle number curve shows an upward trend with a constant slope, it indicates that the laminate has entered the stable crack extension stage. When the slope of its resistance change rate-cycle number curve begins to increase, it indicates that the laminate has entered the unstable crack extension stage. When the resistance change rate-cycle number curve suddenly increases, it indicates that the laminate has suffered overall fracture failure. Step 4.2: The initial resistance value of the sensor unit arranged on the GLARE layer is recorded as R0; the real-time resistance change of the sensor unit is recorded as ΔR, that is, the real-time resistance value R minus the initial resistance value R0; the real-time resistance change rate of the sensor unit is recorded as ΔR / R0; the resistance change rate when the layer enters the stable crack expansion stage is recorded as ΔR / R 0(S) The resistance change rate of the laminate at the critical point between stable and unstable crack extension is recorded as ΔR / R 0(M) The resistance change rate before the fatigue fracture of the laminate is recorded as ΔR / R 0(U) ; When the laminate is in the stable crack extension stage, the residual fatigue life of the laminate is predicted according to formula (1); when the laminate is in the unstable crack extension stage, the residual fatigue life of the laminate is predicted according to formula (2); Where F r is the remaining fatigue times of GLARE laminate, F S F is the total number of fatigue cycles that the crack can withstand during the stable expansion stage. U It is the total number of fatigue cycles that the crack can withstand during the unstable expansion stage.

8. The method for predicting the residual fatigue life of a GLARE laminate structure based on micro-nano sensors according to claim 7 is characterized in that: In the step 4, when the fatigue test is performed, the resistance measuring instrument is connected to the flexible printed circuit of the sensor, and the acquisition frequency of the resistance measuring instrument needs to be greater than the fatigue load frequency.

Citation Information

Patent Citations

  • Sensor for monitoring composite material liquid forming process and preparation method

    CN111044086A